VISCOUS FLUID MOTION IN CYLINDER EXECUTING REGULAR PRECESSION - Гураль, Інеса Михайлівна; Гамарник, Олександр Тимофійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The solution of the linearized Navier-Stokes equations for determining the steady relative motion of viscous incompressible fluid partly filling a cylindrical vessel executing slow regular precession with an arbitrary angle of nutation is constructed. The axial component of the moment of the forces exerted by the fluid on the lateral surface of the vessel is determined.